Using yeast to determine the functional consequences of mutations in the human p53 tumor suppressor gene: An introductory course‐based undergraduate research experience in molecular and cell biology. Issue 2 (22nd November 2016) - Hekmat‐Scafe, Daria S.; Brownell, Sara E.; Seawell, Patricia Chandler; Malladi, Shyamala; Imam, Jamie F. Conklin; Singla, Veena; Bradon, Nicole; Cyert, Martha S.; Stearns, Tim
Abstract: The opportunity to engage in scientific research is an important, but often neglected, component of undergraduate training in biology. We describe the curriculum for an innovative, course‐based undergraduate research experience (CURE) appropriate for a large, introductory cell and molecular biology laboratory class that leverages students′ high level of interest in cancer. The course is highly collaborative and emphasizes the analysis and interpretation of original scientific data. During the course, students work in teams to characterize a collection of mutations in the human p53 tumor suppressor gene via expression and analysis in yeast. Initially, student pairs use both qualitative and quantitative assays to assess the ability of their p53 mutant to activate expression of reporter genes, and they localize their mutation within the p53 structure. Through facilitated discussion, students suggest possible molecular explanations for the transactivation defects displayed by their p53 mutants and propose experiments to test these hypotheses that they execute during the second part of the course. They use a western blot to determine whether mutant p53 levels are reduced, a DNA‐binding assay to test whether recognition of any of three p53 target sequences is compromised, and fluorescence microscopy to assay nuclear localization. Students studying the same p53 mutant periodically convene to discuss and interpret their combined data. The course culminates in a poster session during which students present their findings to peers, instructors, and the greater biosciences community. Based on our experience, we provide recommendations for the development of similar large introductory lab courses. © 2016 by The International Union of Biochemistry and Molecular Biology, 45(2):161–178, 2017.